Pengaruh Bonus Demografi Dan Tingkat Pendidikan Terhadap Pertumbuhan Ekonomi Di Indonesia Periode 2015-2024 - Ladjambu, Hanifa; Saleh, Sri Endang; Payu, Boby Rantow (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to determine the effect of demographic bonuses and education levels on economic growth in Indonesia during the period 2015 – 2024. This is a quantitative study using secondary data obtained from the Central Statistics Agency (BPS). Using panel data regression from 34 provinces in Indonesia over a 10-year period (2015-2024), the data analysis model used is the “Fixed Effect Model (FEM)” panel regression. The results of the study found that (1) The dependency ratio has a negative and insignificant effect on economic growth in Indonesia. This shows that an increase in the dependency ratio tends to be followed by a decrease in yhe dependecy ratio. However, this relationship is not statistically significant. (2) The labor force participation rate variabel has a positive and significant effect on economic growth in Indonesia. This mean that the higher the involvement of the working-age population in economic activities, the greater their contribution to economic growth. (3) The average length of cshoolling variable has a negative and significant effect on economic growth in Indonesia. This indicates that an increase in the average length of schooling has not been accompanied by improvements in the quality and relevance of education, so that graduates tend to be unable to contribute optimally to productivity and economic development.